Can Electroacupuncture Be Useful in Opioid-Induced Hyperalgesia? A Case Report - Marco Di Carlo; Antonio D'Addario; Fausto Salaffi (Medical Association of Pharmacopuncture Institute, 2023)
Opioid-induced hyperalgesia (OIH) is characterized by a paradoxical increase in pain sensitivity following opioid exposure. Although animal models indicate that electroacupuncture (EA) is effective against pain sensitization, there are no reports of its clinical application in OIH treatment. This case report involves an adult patient with osteomalacia complicated by multiple vertebral fragility fractures. The patient developed OIH following the use of oxycodone to treat severe disabling lower back pain that was refractory to nonsteroidal anti-inflammatory drugs. After hospitalization and treatment with low EA-frequency (2-10 Hz) sessions, the patient exhibited significant pain reduction and functional recovery after the first session, which was accompanied by steady progressive improvement as the treatment continued. This case report illustrates the clinical efficacy of EA in OIH treatment and indicates that EA, which has multiple modes of action on the neurobiology of chronic pain, has potential applications in the management of complex and difficult-to-manage conditions, such as OIH.